2007
DOI: 10.1074/jbc.m606056200
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Membrane Fusion and Proteolysis on SpoIIQ Dynamics and Interaction with SpoIIIAH

Abstract: The onset of engulfment-dependent gene expression during Bacillus subtilis sporulation requires the forespore membrane protein SpoIIQ, which recruits mother cell proteins involved in late gene expression to the outer forespore membrane. Engulfment activates the late forespore transcription factor G , which produces high levels of the secreted SpoIVB protease that is required for activation of the late mother cell transcription factor K . Engulfment also triggers the proteolytic cleavage of SpoIIQ, an event tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 37 publications
1
24
1
Order By: Relevance
“…The first is that Q may undergo a change in topology such that Tyr-28 gains access to the cytosol. Intriguingly, Q is subject to proteolysis by the secreted protease SpoIVB at a site not far downstream of the TMD (after Val-72), resulting in an N-terminal fragment that becomes cytosolic (45,46). However, we have found that csfB expression is not misregulated in a strain in which spoIVB is deleted (our unpublished results), arguing against a model in which a SpoIVBgenerated fragment of Q is responsible for csfB regulation.…”
Section: Discussioncontrasting
confidence: 38%
“…The first is that Q may undergo a change in topology such that Tyr-28 gains access to the cytosol. Intriguingly, Q is subject to proteolysis by the secreted protease SpoIVB at a site not far downstream of the TMD (after Val-72), resulting in an N-terminal fragment that becomes cytosolic (45,46). However, we have found that csfB expression is not misregulated in a strain in which spoIVB is deleted (our unpublished results), arguing against a model in which a SpoIVBgenerated fragment of Q is responsible for csfB regulation.…”
Section: Discussioncontrasting
confidence: 38%
“…The interaction with SpoIIQ is necessary for the septal localization and stability of SpoIIIAH (4,5,30). This suggests that SpoIIQ should be necessary for the forespore accessibility and stability of SpoIIIAH-BAP.…”
Section: Degradation Of the Putative Channel After Engulfmentmentioning
confidence: 99%
“…FRAP experiments were conducted as previously described (35,36). Briefly, photobleaching experiments to assess the mobility of S105-GFP (or derivatives) used cells grown in liquid culture (0.25× LB, 0.5 μg/mL of FM 4-64); 10 μL of cells were removed at the indicated times and applied to coverslips.…”
Section: Methodsmentioning
confidence: 99%